Substrate, catalyst, and solvent: the triune nature of multitasking reagents in hydroboration and cyanosilylation - Dixit, Ruchi; Bisai, Milan Kumar; Yadav, Sandeep; Yadav, Vinita; Sen, Sakya S.; Vanka, Kumar (Organometallics, 2021)
A truly green chemical process would avoid the use of an external catalyst, while still achieving high efficiency. This has been realized in the very recent past for hydroboration, cyanosilylation, acetalization, and the aza-Michael addition, among other reactions. The current combined computational and experimental study unlocks the secret to how this highly desirable outcome is accomplished: one of the reactants in the process also acts as the catalyst. Specifically, this is shown (i) for the important hydroboration reaction, with pinacolborane (HBpin) as the hydroborating reagent and benzaldehyde, acetophenone, benzoic acid and p-methoxyphenylacetylene as the hydroborated substrates, and (ii) for cyanosilylation, with trimethylcyanosilane (TMSCN) as the cyanosilylating agent and benzaldehyde as the substrate. The mechanistic understanding thus gained has then been further exploited experimentally to bring hydroboration and cyanosilylation closer to experimental conditions in catalysis. These insights can potentially be expanded to the rapidly growing area of solvent-free and internal catalyst chemistry.